First record of Ophionyssus natricis (Gervais) (Acari: Macronyssidae) on Python reticulatus (Schneider) (Pythonidae) in Brazil - da Silva, Ademar Ferreira; Pinto, Zeneida Teixeira; Teixeira, Rodrigo Hidalgo; Cunha, Rodolfo Armando; Carriço, Cesar; Caetano, Rebecca Leal; Gazeta, Gilberto Salles; Amorim, Marinete (EntomoBrasilis, 2018)
Abstract. Ophionyssus natricis (Gervais) frequently parasitizes snakes kept under human care. This mite is known to mechanically transmit the bacteria Proteus hydrophilus, which can cause hemorrhagic sepsis in snakes. This is the first record of O. natricis mite in Python reticulatus (Schneider) collected in captivity, in Brazil. The micrographs and drawings generated in this study, based on optical light microscopy and SEM observations, highlight an important identifying characteristic of O. natricis: The dorsal surface has two shields, consisting of propodosomal and pygidial, and the ventral surface has only the sternal shield trapezoidal with two pairs of setae, and pores on the edge. The identification of adults female of O. natricis mites in P. reticulatus collected in wild animals kept under human care, in Brazil, provides additional anatomical information to help identify the species by providing more necessary information to understand the morphology of snake mites. Primeiro registro de Ophionyssus natricis (Gervais) (Acari: Macronyssidae) em Python reticulatus (Schneider) (Pythonidae) no Brasil Resumo. Ophionyssus natricis (Gervais) frequentemente parasita cobras mantidas sob cuidados humanos. Este ácaro é conhecido por transmitir mecanicamente a bactéria Proteus hydrophilus, que pode causar sepse hemorrágica em cobras. Este é o primeiro registro O. natricis em Python reticulatus (Schneider) coletados em cativeiro, no Brasil. O estudo foi realizado com o auxílio de microscopia óptica e observações de MEV, gerando desenhos e micrografias, o que permitiu observar importantes características de identificação da fêmea de O. natricis: superfície dorsal com dois escudos, consistindo em propodossoma e pigidial, já a superfície ventral possui apenas o escudo esternal com forma trapezoidal, com dois pares de cerdas e poros na borda. A identificação das fêmeas adultas de O. natricis coletados em P. reticulatus mantidas sob cuidados humanos no Brasil, fornece informações anatômicas adicionais para ajudar na identificação da espécie fornecendo mais informações necessárias na compreensão da morfologia dos ácaros das cobras.